PENERAPAN DESAIN 3D UNTUK MENINGKATKAN EFEKTIVAS PERENCANAAN PEMBANGUNAN BUMDES SEKARMOJO - Evi Fitria Novitasari; Rahma Dila Nurlaili; Akmal Farrel Maulana; Gladys Suci Rahma Yuniar (Jendela Inovasi Daerah, 2026)
This study is motivated by the limited competence and knowledge of BUMDes management in Sekarmojo Village, which has relied solely on 2D design in development planning, resulting in slow development processes and low community participation. Therefore, this study aims to analyze the role of 3D design implementation in improving the effectiveness of BUMDes development planning and communication. This research employs a qualitative approach using a case study method conducted through participatory observation, semi-structured interviews, document review, and assistance in developing 3D designs with village officials. The results show that 3D visualization provides a clearer and more realistic representation of the BUMDes spatial layout, thereby strengthening village officials’ understanding and encouraging community involvement in development deliberations. In addition, the use of 3D design accelerates the decision-making process, as indicated by the approval of the BUMDes development plan starting in September 2025. Thus, the study concludes that 3D design functions not only as a technical tool but also as an effective communication medium to enhance transparency, participation, and efficiency in village development planning.